2021
DOI: 10.1167/iovs.62.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Dominance and Functional Asymmetry in Visual Attention Networks

Abstract: Purpose The dorsal attention network (DAN) and the ventral attention network (VAN) are known to support visual attention, but the influences of ocular dominance on the attention networks are unclear. We aimed to explore how visual cortical asymmetry of the attention networks correlate with neurophysiological oscillation and connectivity markers of attentional processes. Methods An oddball task with concentric circle stimuli of three different sizes (i.e., spot size of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Therefore, the two attention control networks integrate more strongly to support this task more efficiently. These results also provide converging evidence for the theory that the DAN and VAN are not isolated in the process of controlling attention but interact to achieve dynamic control of attention [ 45 , 54 ].…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, the two attention control networks integrate more strongly to support this task more efficiently. These results also provide converging evidence for the theory that the DAN and VAN are not isolated in the process of controlling attention but interact to achieve dynamic control of attention [ 45 , 54 ].…”
Section: Discussionsupporting
confidence: 55%
“…This was confirmed by Coren and Porac 8 and Coren 9 . Later, Shneor and Hochstein 10 , 11 demonstrated that the DE has an advantage in more elaborate tasks like visual feature or conjunction search, which has also been verified recently by Liu et al 12 . At the neuronal level, stimulation of the DE resulted in higher and shorter visually evoked potentials when using electroencephalography 13 (see also 14 ) and in larger visual areas activation when using functional imagery 15 .…”
Section: Introductionmentioning
confidence: 54%
“…However, given that most tasks require regions that belong to the SAL and DAN networks, it is not clear what would be the performance in a visually oriented task. It is known that the DAN is activated by visual-spatial attention tasks 38 , connected to the ventral attention network 39 and related to visual attention modulated from the ocular dominance 40 . Also, it has been shown that DAN FC changes after acute stress exposure 41 and in sleep problems 42 .…”
Section: Discussionmentioning
confidence: 99%